University of Massachusetts Medical School (UMMS): (Small Methods 9/2018). Issue 9 (14th September 2018) - Unknown
Abstract : This special section in Small Methods portrays a small sample of the innovative life science research at UMMS. This collection of papers spans a wide disciplinary range that includes biomedical engineering/materials science, frontiers in optical microscopy, and organic synthesis, as well as nanoparticle technology and emerging CRISPR‐based genomic sciences.